Investigating factors affecting project performance moderated by project governance - Al Alyani, Wafa Rashid; Lee, Chia Kuang (LLC “Consulting Publishing Company “, 2024)
The purpose of this study is to empirically examine the impact of total quality management, institutional pressure, and organizational citizenship behavior on project performance moderated by project governance in ongoing construction projects. Empirical data were collected from 162 respondents engaged in ongoing construction projects in Oman using a self-administered questionnaire. The partial least square structural equation modeling (PLS-SEM) technique was used to analyze the data. The findings show that TQM significantly impacts project performance. In contrast, organizational citizenship behavior did not mediate between total quality management and project performance. Project governance partially moderated the impact of total quality management on project performance. This study offers practical implications for the construction industry that wants to improve its project performance. This paper recognizes the significance of TQM practices by developing an industry-wide culture of successful project performance. It is vital to support the ongoing efforts of the project managers to promote and apply quality management principles, particularly in the construction industry.